Elaborarea schemei tehnologice de obtinere a unor principii bioactive din biomasa de alge cianofite [Articol] - Bulimaga, Valentina; Zosim, Liliana; Pisova, Maria; Şalaru, Vasile; Ţurcanu, Olga; Trofim, Alina (CEP USM, 2014)
The technological scheme of obtaining of phycoerythrin, phycocyanin, microcystins, endo– and exopolysaccharides from the blue green algae biomass in a single technological process has been developed and a sorbent for the separation of microcystins and phycobiliproteins have been proposed.